HIGHER DIMENSIONAL UNIVERSE IN SCALAR-TENSOR THEORY - Singh, S Surendra (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
We consider the Kaluza-Klein type cosmological model in scalar-tensor theory proposed by Lau and Prokhovnik. The exact solution of the field equations are obtained by using the gamma law equation of state, $p =(γ - 1) ρ$ in which the parameter $γ$ depends on scale factor $R$. The functional form of $γ(R)$ is used to describe a wide range of cosmological solution at early universe for two phases in cosmic history: inflationary phase and radiation dominated phase. The solutions show the power law expansion and cosmological constant is found to be positive and decreasing function of cosmic time. The solutions are compatible with the Dirac's large number hypothesis. The deceleration parameter has been presented in a unified manner in terms of scale factor which describes the inflation of the model.